On short-time bilinear Strichartz estimates and applications to the Shrira equation. (September 2020) - Schippa, Robert
Abstract: Short-time bilinear Strichartz estimates for Schrödinger-like equations on tori are proved, which resemble the bilinear Strichartz estimates on Euclidean space. By this and a known combination of perturbative and energy arguments, we improve the well-posedness theory for the Shrira equation.